2007
DOI: 10.1007/s11096-007-9135-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Patterns in Amman, Jordan

Abstract: Self-medication is a common health care practice in Jordan, where people are becoming increasingly familiar with drugs and their brand names. Self-medication behavior varied significantly with a number of socio-economic factors. Unfortunately, only a small percentage of patients engaged pharmacy personnel in therapeutic consultations beyond briefly mentioning a symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
164
6
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(209 citation statements)
references
References 27 publications
27
164
6
12
Order By: Relevance
“…These findings suggest that pharmacists in lower socioeconomic areas have a greater responsibility in meeting the needs of patients who have chronic conditions. These results are in agreement with those of a study conducted in Canada where it was observed that clinical specialist services were comparatively underutilized by people living in areas of lower socioeconomical circumstances [10]. The fact that in our study pharmacists were preferred over GPs for review of treatment for chronic conditions in both districts of Amman further supports the positive attitude towards the role of the community pharmacist in Amman.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings suggest that pharmacists in lower socioeconomic areas have a greater responsibility in meeting the needs of patients who have chronic conditions. These results are in agreement with those of a study conducted in Canada where it was observed that clinical specialist services were comparatively underutilized by people living in areas of lower socioeconomical circumstances [10]. The fact that in our study pharmacists were preferred over GPs for review of treatment for chronic conditions in both districts of Amman further supports the positive attitude towards the role of the community pharmacist in Amman.…”
Section: Discussionsupporting
confidence: 93%
“…Understanding these roles in the community setting and whether they meet the needs of the patient has become imperative. This study derives from the fact that in Jordan, community pharmacies are the most accessible primary health care facilities [10] In addition, this is the first study in Jordan to assess differences in patient perspective of the role of the community pharmacist based on differences in socioeconomic background.…”
Section: Discussionmentioning
confidence: 99%
“…Our estimates are lower than the figures reported from the previous study conducted in Alexandria in 2009; it was found that 81.1% of participant practiced self-medication [11]. Similarly, in Karachi, a study was conducted and it was found that selfmedication was prevalent among 76% of the population [12]. On the contrary, another study among Jordanian population showed lower prevalence (42.5%) [13].…”
Section: Discussioncontrasting
confidence: 84%
“…Selfmedication is the most common cause of poisoning in the world.Adventitious and irrational use of medicines not only does not help the patient's health, but also because of side effects and complications can cause serious problems. [1][2][3] Today, the indiscriminate use of drugs and generally selfmedication known as the health and socio-economic problems in various countries such as Iran. Unfortunately, in developing countries, the use of drugs has long roots.…”
Section: Introductionmentioning
confidence: 99%